ANALISIS KUANTITATIF IMPLEMENTASI KEBIJAKAN PROGRAM BPJS KESEHATAN DI RSUD PROF. DR. ALOEI SABOE KOTA GORONTALO - Abdussamad, Siti Nurcahyati; Abdussamad, Siti Nurmardia (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This research aims to determine the extent to communication and resources have on the effectiveness of the implementation of the BPJS Health program, both simultaneously and partially. The background to the problem of implementing the BPJS Health program is that for approximately 5 years, the BPJS Health program has always experienced a budget deficit. The main cause is the categories of BPJS Health participants who tend not to pay premiums on time and participants who only pay contributions when he just wanted to go to the hospital for treatment. This research uses quantitative research methods. The data collection technique is by distributing questionnaires to 100 samples who are BPJS Health users at RSUD Prof. Dr. Aloei Saboe, Gorontalo City. The research results show that communication and resources have a partial positive and significant influence of 21.8% and 62% respectively on the effectiveness of the implementation of the BPJS Health program and simultaneously the influence of communication and resources on the effectiveness of implementing the BPJS Health program was 61.3%.